2006
DOI: 10.1096/fj.05-4017fje
|View full text |Cite
|
Sign up to set email alerts
|

PS2 mutation increases neuronal cell vulnerability to neurotoxicants through activation of caspase‐3 by enhancing of ryanodine receptor‐mediated calcium release

Abstract: Increase of neuronal cell vulnerability by presenilin-2 (PS2) mutation by increase of caspase-3 activity through ryanodine receptor-mediated perturbation of calcium homeostasis was investigated. Stably transfected PC12 cells and cortical neurons from transgenic mice expressing mutant PS2 (N141I) showed a significantly enhanced sensitivity to L-glutamate, Aβ 25-35 , and Aβ 1-42 (ADDLs form) compared with cells expressing wild-type PS2. Consistent with this result, much greater intracellular calcium levels and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Consistent with normal cell differentiation, and similar to what was observed in the brains of nontrangenic mice in a previous study (Lee et al, 2005), RyR was detectably expressed in the neuronal cells of nontransgenic mice (data not shown). RyR expression was detected in neuronal cells, and it was found to be increased by treatment with caffeine (30 mM), an RyR agonist during cell differentiation; visualized by immunocytochemistry with fluorescence dye ( Fig.…”
Section: Increased Expression Of Ryanodine Receptor and Calcium Releasupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with normal cell differentiation, and similar to what was observed in the brains of nontrangenic mice in a previous study (Lee et al, 2005), RyR was detectably expressed in the neuronal cells of nontransgenic mice (data not shown). RyR expression was detected in neuronal cells, and it was found to be increased by treatment with caffeine (30 mM), an RyR agonist during cell differentiation; visualized by immunocytochemistry with fluorescence dye ( Fig.…”
Section: Increased Expression Of Ryanodine Receptor and Calcium Releasupporting
confidence: 90%
“…In addition, it was reported that PS2 interacts with sorcin, a modulator of RyR (Pack-Chung et al, 2000). Our previous data also show that PS2 colocalizes with type 3 RyR in neurons (Lee et al, 2005). Therefore, our data suggest that alterations of RyR may be involved in the PS2 mutation-induced disruption of neuronal cell differentiation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Cell cultures were then maintained at 37jC in a humidified atmosphere with 5% CO 2 . RAW 264.7 macrophage cells (16) and primary neuronal cells (17) were prepared and cultured as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, RyanR protein levels and channel function are increased in mouse models of containing PS mutations PS1-M146V and PS2-N141I [41][42][43]. Clinical mutations of PS2 also enhanced Ca 2+ release from IP 3 R-gated ER stores [44].…”
Section: Presenilins and Intracellular Calcium Signalingmentioning
confidence: 99%